Investigation of rGO and chitosan effects on optical and electrical properties of the conductive polymers for advanced applications - Ozkan, Betul Cicek; Soganci, Tugba; Turhan, Huseyin; Ak, Metin (Pergamon-Elsevier Science Ltd, 2019)
A simple and fast method for preparing chitosan (CH)/conducting polymer (CP) composite film with and without reduced graphene oxide (rGO) was realized to investigate the effect of rGO on an optoelectrochemical system. For this purpose, firstly rGO was successfully dispersed in the acidic aqueous solution of CH by ultrasonic agitation. One by one CH and CH/rGO blend deposited on an indium tin-oxide (ITO) coated glass electrode by drop-casting method. After that, N-1,N-4-bis(2,5-di(thiophen-2-yl)-1H-pyrrol-1-yl) terephthalamide (m(BT)) electroactive monomer was deposited onto CH and CH/rGO modified ITO electrode surfaces via electrochemical polymerization. Electrochemical and optical properties of the composite structures were investigated by cyclic voltammetry (CV) technique and UV-vis spectroscopy. The surface characterizations of nanocomposites have been performed by scanning electron microscopy. It was observed that, chemical functionalities of CH, rGO and p(BT) provide excellent compatibility. Therefore, the CH/rGO/p(BT) electroactive nanocomposite has better conductivity, stability, charge density, electrochromic switching kinetics and electrochemical properties than the CH/p(BT) and p(BT)/rGO composites. This is due to more efficient synergistic effect between CH, rGO and p(BT) which provide larger active surface area and ease ion transport. This method for producing composite films with novel optical, electrical and stability properties has been gaining a new perspective in the material world, which enables smart and advanced material design in various practical applications especially for designing molecular detection systems. (C) 2018 Elsevier Ltd. All rights reserved.
Keywords: Chitosan; Conducting polymer; rGO; Spectroelectrochemistry